Emma Thompson and the Nanny McPhee Tales - Thompson, Emma; Goodman, Martin (The University of Hull)
The actor and writer, Emma Thompson, comes to Hull for the first annual children’s writing events. Emma stars as the returning Nanny McPhee in the film Nanny McPhee and the Big Bang, and also wrote the script. With a character based on the Nurse Matilda stories, this new film sprang from Emma’s imagination and is also appearing as an original novel.